Comparison of the effects of lockdown due to COVID-19 on glucose patterns among children, adolescents, and adults with type 1 diabetes: CGM study. Issue 2 (28th October 2020) - Di Dalmazi, Guido; Maltoni, Giulio; Bongiorno, Claudio; Tucci, Lorenzo; Di Natale, Valeria; Moscatiello, Simona; Laffi, Gilberto; Pession, Andrea; Zucchini, Stefano; Pagotto, Uberto
Abstract : Introduction: The COVID-19 pandemic forced the Italian government to issue extremely restrictive measures on daily activities since 11 March 2020 ('lockdown'), which may have influenced the metabolic control of type 1 diabetes mellitus (T1D). The aims of the study were to investigate continuous glucose monitoring (CGM) metrics in children and adults with T1D during lockdown and to identify their potentially related factors. Research design and methods: We enrolled 130 consecutive patients with T1D (30 children (≤12 years), 24 teenagers (13–17 years), and 76 adults (≥18 years)) using either Dexcom or FreeStyle LibreCGM>70% during the study period, without hybrid closed-loop insulin pump. CGM metrics during the 20 days before and the 20 days after lockdown were calculated. By telephonic contact, we performed validated physical activity and perceived stress questionnaires. Results: In children, significantly lower glucose SD (SDglu) (p=0.029) and time below range (TBR)<54 mg/dL (TBR2) (p=0.029) were detected after lockdown. CGM metrics were comparable in teenagers before and during lockdown. After lockdown, adults improved significantly time in range (TIR) 70–180 mg/dL (p<0.001) and remaining metrics, except percent coefficient of variation and TBR2. In adults, considering the changes in SDglu and TIR occurred before and during lockdown, we identified a group with improved TIR and SDglu who performed more physical activity, one with improved glucose variability who was younger than the other patients, and one with worsened glucose variability who showed higher perceived stress than others. Conclusion: In patients with T1D during lockdown, CGM metrics mostly improved in children and adults, whereas it was unchanged in teenagers. In adults, age, physical activity, and perceived stress may be relevant contributing factors.